Polish LGBTQ+-Related Anglicisms in a Language Contact Perspective - Witalisz, Alicja (Studia Anglica Posnaniensia, 2021)
Research on anglicisms in Polish has nearly a century-long tradition, yet it was Jacek Fisiak’s 1960s–1980s studies on English loanwords that initiated continuous academic interest in anglicisms, coinciding with more intensive English-Polish language contact in post-war Poland. While English loans have been well-researched in the last four decades, the ongoing intensity of English lexical influence on Polish, yielding not only new loans but also new loan types, calls for further studies, especially in the area of quickly developing professional jargons and sociolects. The influx of English-sourced lexis is reflected in the diversity of semantic fields, whose number has grown from 18 (identified in Słownik warszawski 1900–1927) to 45 (Mańczak-Wohlfeld 1995). A semantic field that has been underresearched in studies on Polish anglicisms is the LGBTQ+-related lexis, which has drawn from American English gayspeak, shaped by the post-Stonewall gay rights movement initiated in the 1970s. The language data analysed in this study have been collected in a two-stage procedure, which included manual extraction of anglicisms sourced in a diversified corpus of LGBTQ+-related written texts, published in Polish between 2004 and 2020. The second stage involved oral interviews which served a verification function. The aim of this study is to contribute to the lexicographic attempts at researching English-sourced LGBTQ+-related vocabulary in Polish through its identification, excerption, and classification. Assuming an onomasiological approach to borrowing, we arrange LGBTQ+-related anglicisms on a decreasing foreignness scale to identify the borrowing techniques adopted by the recipient language speakers in the loan nativization process. We also address issues related to the identification and semantics of loans, and sketch areas of research on loan pragmatic functions that need further studies.